RESHAPING CURRICULUM OF INDONESIAN MARITIME EDUCATION AND TRAINING - Bokau, Joe Ronald Kurniawan; Sulistiana, Oktavera (Ridwan Institute, 2024)
Maritime education and training are pivotal for the development and operation of autonomous ships and green port era, encompassing areas such as safety, economic advantages, legal frameworks, cybersecurity, and operational efficiency. The author aims to develop robust and resilience curriculum for future generation which is a combination of well developed STCW (Standard of Training & Certification of Watchkeeping) and Indonesia Educational Standards through literature review and applying a well-designed guidance from the Indonesian Ministry of Education. The research contribution lies in the development of an integrated curriculum that aligns international maritime standards with national educational requirements, using a systematic approach informed by literature and official educational guidance. The data then compared with some MET's curriculum and the results are proven to be aligned with every limitation set up by International Standards and Indonesian National Education Standards.